Highly Emissive Chiral Mn(II) Bromide Hybrids for UV‐Pumped Circularly Polarized LEDs and Scintillator Image Applications. Issue 8 (24th February 2023) - Davydova, Maria P.; Meng, Lingqiang; Rakhmanova, Mariana I.; Bagryanskaya, Irina Yu.; Sulyaeva, Veronica S.; Meng, Hong; Artem'ev, Alexander V.
Abstract: Organic–inorganic hybrid metal halides are a promising platform for the design of materials for circularly polarized luminescence (CPL) and X‐ray detection applications. Meanwhile, despite the recent progress in this hot field, hybrid metal halides, simultaneously endowed with efficient CPL and high photoluminescence quantum yield (PLQY), are still limited to a few examples. Herein, the efficient, stable, and low‐cost CPL‐active Mn(II) hybrids are developed via blending of luminogenic [MnBr4 ] 2− anions with N/OH‐bond free R / S ‐[MBA‐Me3 ] + cations in a single ionic structure. The synthesized R / S ‐[MBA‐Me3 ]MnBr4 hybrids display brightly green Mn 2+ ‐centered circularly polarized phosphorescence with near‐unity PLQY and a high g lum factor of 0.0045. Single crystals of R / S ‐[MBA‐Me3 ]MnBr4 are used to fabricate UV‐pumped circularly polarized light‐emitting diodes (LEDs) displaying a high optical selectivity upon exposure to right‐handed and left‐handed circular polarization conditions. Moreover, the titled compounds are found to emit strong X‐ray radioluminescence with excellent linear response to X‐ray dose rate that is used for X‐ray imaging demonstration. These findings reveal a great potential of R / S ‐[MBA‐Me3 ]MnBr4 as low‐cost materials for CPL‐LEDs, scintillators, and X‐ray imaging applications. Abstract : New Mn(II) hybrids showing circularly polarized luminescence (CPL) with near‐unity photoluminescence quantum yield and a high disymmetry factor g lum are designed. The application of these hybrids is demonstrated by the fabrication of UV‐pumped CPL light emitting diodes with excellent optical selectivity. Besides, these hybrids reveal efficient X‐ray scintillation properties with a linear response to X‐ray dose rate and excellent radiostability.